A Study of Prevalence and Predictors of Acute Ischemic CVA Patients Admitted to Manipal Teaching Hospital, Pokhara, Nepal - Jwarchan, Bishnu; Yogi, Nikunja; Adhikari, Suman; Bhandari, Prabin; Lalchan, Subita (Eastern Green Neurosurgery, 2020)
Background: According to the World Health Organization (WHO), 15 million people suffer stroke worldwide each year. Of these, 5 million die, and another 5 million are left permanently disabled.Materials and methods: A retrospective hospital based observational study was carried out in patients with ischemic CVA. Modified Ranking Scale (MRS) on the follow up on 30 days after discharge was obtained. MRS 0-2 was categorized and good outcome and MRS 3-6 was categorized as poor outcome.Results: Out of 56 patients studied 33.9 % were less than 60 years of age and 63.1% were greater than 60 years of age. Male to female ratio was 1.55. MCA territory infarct was the most common with the frequency of 76.8%. There was significant association of HTN, DM, coronary artery disease and other factors as well with the outcome of the patients.Conclusion: On regards to clinic-social demographic parameters there was statistical significance between the gender of the patient, history of systemic hypertension, history of diabetes mellitus and coronary artery disease and outcome of the patient in 30 days follow up.